Association Between Sleep Duration And Body Mass Index (PUSA Journal of Hospitality and Applied Sciences, 2019)
Background: Sleep is one of the important and familiar parts of everyone’s life. It is one  of the three pillars along with nutrition and exercise. Objective: The purpose of the present  study is to find the association if exists, between self-reported sleep duration with Body mass  index. Methodology: This is an exploratory study done in New Delhi, India among 100 adults  aged 20-40 years using opportunity sampling method. Data on socio-demographic profile,  self-reported sleep duration, body mass index were gathered from 100 subjects. Results: A  significant negative correlation (p=.002) was observed between body mass index and self  reported sleep duration. Conclusion: The current study establishes an association between  the less duration of sleep and body mass index, which predisposes an individual for risk of  developing Non-communicable diseases.
Keywords: Sleep; Body mass index; Non-communicable diseases; Nutrition; Exercise